Іmperfection of the scientific methodproviding an assessment of the efficiency of investments - Goyko, A.F.; Sorokina, L.V. (Ways to Improve Construction Efficiency, 2023)
The article is devoted to issues related to the imperfection of the scientific and methodological tools and the shortcomings of the objective assessment of the economic efficiency of investment projects in the conditions of an acute shortage of investments and a decrease in the efficiency of investment activities observed recently. One of the main conditions for the acceleration of economic growth is the improvement of the system for selecting investment projects for implementation, which is carried out by evaluating the effectiveness of investment activities using a number of indicators that influence investment decisions. It is indicated that when evaluating the efficiency of complex processes, which includes the investment process, it is generally impossible to unequivocally state the priority of one or another indicator, and it is better to use a system of performance evaluation indicators. Examples are given from the practice of justifications for investment performance evaluation, the analysis of the results of which indicates the imperfection and shortcomings of individual performance indicators and helps to identify new problematic issues of investment evaluation. The essence of individual indicators is revealed and the role of each of them is analyzed, their influence on the correctness of the final decision is substantiated. The research proposes methods of harmonizing intermediate indicators of the net present value using a weighted average generalizing indicator and methods of fuzzy multi-criteria optimization. Although the significant advantage of the last methodical approach, which is manifested by the higher values of its weighting factor when summarizing the partial indicators of NRV, and increases the differences in the advantages of one or another project, but "soft calculations" allow to justify the minimum economic effect that capital investment should provide. Also, a vaguely multiple approach makes it possible to justify the degree of satisfaction of investors' goals in the case of receiving just such a reduced cash flow, instead of the one provided for in the project. Decisions made taking into account the tools for evaluating the effectiveness of investment projects will contribute to the acceleration of the economic growth of our country.